Flow Cytometric Expression of CD49d in Newly Diagnosed Chronic Lymphocytic Leukemia and Its Correlation with Established Prognostic Markers - Kunnumbrath, Arathi; Singh, Neha; Gupta, Arvind Kumar; Chowdhury, Nilotpal; Nath, Uttam Kumar; Chandra, Harish (Journal of Laboratory Physicians, 2022)
Introduction Chronic lymphocytic leukemia (CLL) is the commonest hematological malignancy in the West but is relatively uncommon in India. The prognosis of CLL is determined by well-established prognostic markers. CD49d has been emerging as a promising prognostic marker in CLL. CD49d expression in CLL has been found to have an aggressive clinical course, shorter time to first treatment, and poorer prognosis. The aim of this study was to analyze the flow cytometric expression of CD49d in newly diagnosed CLL and to correlate its expression with clinico-hematological parameters.Materials and Methods Twenty-five consecutive patients of CLL, diagnosed on flow cytometry, were included in the study. Patients on treatment or those with relapse were excluded. The panel for flow cytometry included the routine markers used for CLL diagnosis along with CD49d. The expression of CD49d was correlated with clinico-hematological parameters in all patients. “R” software was used for the statistical analysis. Fisher's exact test and Wilcox test were used to assess the correlation of CD49d to categorical and continuous data, respectively.Results The mean age of the patients was 62.6 ± 12.5 years, and 80% were symptomatic at diagnosis. CD49d expression was found in 44% cases, with a higher proportion being male patients. CD49d and prolymphocyte percentage showed a statistically significant correlation (p = 0.0007). We found a statistically significant correlation between CD49d expression and lymphadenopathy and splenomegaly with p-values of 0.033 and 0.0472, respectively. CD49d positivity correlated significantly with a higher Rai stage (p = 0.0196) and intermediate and high-risk cases according to Binet staging (p = 0.033).Conclusion CD49d expression in the present study correlated with a higher prolymphocyte percentage, lymphadenopathy, splenomegaly, and higher Rai and Binet stages. CD49d expression on flow cytometry was reproducible and easy to interpret.
Keywords: CD49d; Chronic lymphocytic; flow cytometry; leukemia; prognosis